PERLINDUNGAN HUKUM BAGI ANAK YANG MENJADI PERANTARA DALAM JUAL BELI NARKOTIKA - Ayu Nadya Gayatri; Made Sugi Hartono; Ni Ketut Sari Adnyani (Jurnal Ilmu Hukum Sui Generis, 2023)
This research aims to (1) determine the form of legal protection for children who become intermediaries in buying and selling narcotics, and (2) to find out the appropriate sanctions imposed on children who become intermediaries in buying and selling narcotics. The type of research used in this research is a type of normative legal research which aims to examine the application of law regarding children involved in narcotics crimes. This research uses a statutory approach (statue approach), conceptual approach (conceptual approach) and case approach (case approach). This research is supported by statutory regulations, namely Law No. 35 of 2014 concerning Child Protection and Law No. 11 of 2021 concerning the Juvenile Justice System, then from journals, articles, scientific literature that are relevant to the main problem in this research. The results of this research show that (1) there is an appropriate form of legal protection for children who act as intermediaries in cases of buying and selling narcotics, and (2) appropriate sanctions are imposed on children who act as intermediaries in cases of buying and selling narcotic